2021
DOI: 10.3390/diagnostics11050867
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Impairment in Patients Living with HIV: Predictors and Associated Biomarkers

Abstract: Despite the substantial changes resulting from the introduction of combination antiretroviral therapy (cART), the prevalence of HIV-associated neurocognitive disorders (HAND) remains substantial. Blood–brain barrier impairment (BBBi) is a frequent feature in people living with HIV (PLWH) and it may persist despite effective antiretroviral treatment. A cross-sectional study was performed in PLWH who underwent lumbar puncture for clinical reasons or research protocols and several cerebrospinal fluid biomarkers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Likely the external toxic signals are elaborated mainly from inflammatory cells, perhaps predominantly from macrophages and other myeloid cells. Late in infection HIVE also commonly disrupts the blood-brain barrier, further contributing to neuronal injury and dysfunction ( 36 , 88 , 89 ).…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Likely the external toxic signals are elaborated mainly from inflammatory cells, perhaps predominantly from macrophages and other myeloid cells. Late in infection HIVE also commonly disrupts the blood-brain barrier, further contributing to neuronal injury and dysfunction ( 36 , 88 , 89 ).…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Recent studies have also found evidence of endothelial dysfunction and blood-brain barrier (BBB) impairment in ART-treated and virally-suppressed PWH ( Caligaris et al, 2021 ; Ellis et al, 2021 ; Gelman, 2015 ; Kristoffersen et al, 2009 ; Melendez et al, 2008 ; Ross et al, 2009 ). The BBB, composed of specialized endothelial cells and tight junctions and surrounded by a basement membrane, pericytes, astrocytes, microglia and neurons ( Atluri et al, 2015 ; De Benedetto et al, 2020 ; Marincowitz et al, 2019 ), is a primary target of HIV-associated neural injury ( Eugenin et al, 2006 ; Williams et al, 2012 ) and a central neuropathological factor underlying HAND ( Cysique and Brew, 2019 ; Gelman, 2015 ; Gelman et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, CSF HIV-RNA was also associated with albumin ratio, an association that was not as evident in the other groups ( Supplementary Figure 2 ). This might either be a reflection of facilitated penetration of peripheral virions into the CNS or that blood brain barrier impairment leads to an increased inflammatory response resulting in higher levels of locally replicated virus [ 28 ]. CSF HIV-RNA in the CNS OI group was also weakly associated with CSF pleocytosis, a finding previously observed in smaller studies [ 29 , 30 ] and in other CNS coinfections such as neuroborreliosis and herpes zoster [ 20 , 31 ].…”
Section: Discussionmentioning
confidence: 99%